2013
DOI: 10.1523/jneurosci.1854-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

NMDA and GABAB(KIR) Conductances: The “Perfect Couple” for Bistability

Abstract: Networks that produce persistent firing in response to novel input patterns are thought to be important in working memory and other information storage functions. One possible mechanism for maintaining persistent firing is dendritic voltage bistability in which the depolarized state depends on the voltage dependence of the NMDA conductance at recurrent synapses. In previous models, the hyperpolarized state is dependent on voltage-independent conductances, including GABAA. The interplay of these conductances le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…The predictive roles of GABA B and NMDA are in accordance with recent findings that slow synaptic currents mediate persistent activity [55] and stimulus-outcome discrimination [56], respectively. The finding that both iNMDA and iGABA B code for state transitions, presumably by shaping the somatic plateau potential, indicates that the balance of slow excitation/inhibition is crucial for the stability of the persistent state, as proposed by [55].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The predictive roles of GABA B and NMDA are in accordance with recent findings that slow synaptic currents mediate persistent activity [55] and stimulus-outcome discrimination [56], respectively. The finding that both iNMDA and iGABA B code for state transitions, presumably by shaping the somatic plateau potential, indicates that the balance of slow excitation/inhibition is crucial for the stability of the persistent state, as proposed by [55].…”
Section: Discussionsupporting
confidence: 88%
“…The finding that both iNMDA and iGABA B code for state transitions, presumably by shaping the somatic plateau potential, indicates that the balance of slow excitation/inhibition is crucial for the stability of the persistent state, as proposed by [55]. In support of this argument, we found that stable persistent activity trials were characterized by both increased NMDA and GABA B currents, effectively stabilizing the microcircuit activity.…”
Section: Discussionsupporting
confidence: 85%
“…The dynamics of the compartmental voltages and the leak, noise, AMPA, NMDA, GABA-A, and GABA-B conductances are the same as (Sanders et al, 2013) except for the following changes: (1) the maximal conductances were changed, and the ones used in this study are shown in Table 1; (2) the implementation of the external (TS) input was changed and is described below; (3) α in the equation for the NMDA dynamics was changed from 0.1 to 0.5 because NMDA conductance activation required too many spikes [α had an original value of 1 in Lisman et al, 1998 but was changed in Sanders et al, 2013 to reflect the lack of saturation of the NMDA conductance with single spikes (Popescu et al, 2004)]; (4) instead of 25% of the KIR conductance being constitutively active, 5% of the KIR conductance was constitutively active and 95% was activated by GABA-B, giving a modified equation describing the KIR current: IGABAB/KIR=gGABAB/KIR(0.05+0.95Σisi)VdEGABAB/KIR1+exp(0.1(VdEGABAB/KIR+10)) (see Sanders et al, 2013 for definition of all variables).…”
Section: Methodsmentioning
confidence: 99%
“…Whatever the nature of I basal in the brain, it certainly carries important physiological functions. GIRK's basal activity and the balance between I basal and I evoked emerge as important determinants of the level of excitability and resting membrane potential in neurons (Chen & Johnston, 2005;Luscher et al, 1997;Torrecilla, Fernandez-Aedo, Arrue, Zumarraga, & Ugedo, 2013;Torrecilla et al, 2002;Wiser et al, 2006), bistability of some neuronal networks (Sanders, Berends, Major, Goldman, & Lisman, 2013), neuronal plasticity through depotentiation of long-term potentiation (Chung, Ge, et al, 2009;Chung, Qian, Ehlers, Jan, & Jan, 2009;Cooper et al, 2012), depressive behavior (Llamosas, Bruzos-Cidón, Rodríguez, Ugedo, & Torrecilla, 2015), dendritic integration (Makara & Magee, 2013), and possibly in working memory (Sanders et al, 2013), and have been proposed to be related to effects of Li + , a drug used in the treatment of bipolar disorder (Farhy Tselnicker et al, 2014).…”
Section: Central Nervous Systemmentioning
confidence: 99%